The efficacy and safety of novel antiepileptic drugs in treatment of epilepsy of patients with brain tumors - Zhai, Weiwei; Yu, Qiaoling; Wu, Huizhen (Frontiers in Neurology, 2024)
Objective This meta-analysis aimed to assess the effectiveness and safety of novel antiepileptic drugs (AEDs) in treating epilepsy in patients with brain tumors (BTRE). Methods A search was conducted on PubMed, EMBASE, Web of Science, and the Cochrane Library from inception to February 2023, with English language restriction. Results In this meta-analysis, 18 clinical trials involving 755 BTRE patients were included to assess the efficacy and safety of novel AEDs in BTRE treatment. At the last follow-up, a ≥50% reduction in seizure frequency was experienced by 72% of patients (random-effects model, 95% CI = 0.64–0.78) using novel AEDs. At the last follow-up, seizure freedom was experienced by 34% of patients (random-effects model, 95% CI = 0.28–0.41) using novel AEDs. The pooled incidence of AEs was found to be 19% (95% CI: 13%–26%), with a withdrawal rate due to adverse effects of only 3%. Comparable efficacy and incidence of adverse effects were observed between lacosamide and perampanel. Conclusion This meta-analysis suggests that novel antiepileptic drugs are deemed effective for seizure control in brain tumor patients, particularly when used as adjunctive therapy. Although lacosamide and perampanel received more focus in studies, no significant difference was observed in the efficacy and adverse reactions of these two drugs in seizure control. Further randomized controlled trials are deemed necessary to validate our findings.